2020
DOI: 10.1177/1094428120947794
|View full text |Cite
|
Sign up to set email alerts
|

Will the Questions Ever End? Person-Level Increases in Careless Responding During Questionnaire Completion

Abstract: Is there a point within a self-report questionnaire where participants will start responding carelessly? If so, then after how many items do participants reach that point? And what can researchers do to encourage participants to remain careful throughout the entirety of a questionnaire? We conducted two studies (Study 1 N = 358; Study 2 N = 129) to address these questions. Our results found (a) consistent evidence that participants responded more carelessly as they progressed further into a questionnaire, (b) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 29 publications
5
59
0
2
Order By: Relevance
“…Costs (e.g., time or cognitive effort) and benefits (e.g., financial gratification or intrinsic motivation) are set off against each other to evaluate the willingness to further participate at a specific point of time. That is, not only the willingness to answer superficially increases but also the probability to abort the questionnaire ( Bowling et al, 2020 ). Thus, it seems plausible to consider the phenomena of attrition and careless responding in tandem ( Meade et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Costs (e.g., time or cognitive effort) and benefits (e.g., financial gratification or intrinsic motivation) are set off against each other to evaluate the willingness to further participate at a specific point of time. That is, not only the willingness to answer superficially increases but also the probability to abort the questionnaire ( Bowling et al, 2020 ). Thus, it seems plausible to consider the phenomena of attrition and careless responding in tandem ( Meade et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, it has been shown that satisficing degrades the quality of survey results [2], [3], [10]- [13]. In particular, in online questionnaires, this problem is a factor that significantly contributes to quality deterioration [14]. Oppenheimer et al [2] proposed the instructional manipulation check (IMC), which inserts instructions such as "Please move to the next page without answering any question" in the instructional text, and conducted an online questionnaire using the IMC.…”
Section: Related Work and Challengesmentioning
confidence: 99%
“…The intra-subject deviation is the difference between the baseline measured on pages 5 and 6 and the mean of all pages. The reason for adding this deviation is that careless responses increase as the respondents proceed through the questionnaire [14]. Based on this fact, we assumed that the feature difference between the beginning and end of the questionnaire might contribute to the detection of careless responses.…”
Section: A Machine Learning Modelsmentioning
confidence: 99%
“…Additionally, certain scales, such as those that measure socially desirable traits, may facilitate non-random IER whereas other scales that do not necessarily have a socially desirable aspect, may facilitate random IER. It may be that participants read the first few items and construct a schema on how to respond to the items but engage in less effort as they progress through the survey, regardless of pattern ( Bowling et al, 2020 ). Ultimately, while it may be that direct IER is the least-related form of IER to response styles, it can still be assessed within a larger battery of IER assessment, contributing to the holistic determination of IER for participants.…”
Section: Discussionmentioning
confidence: 99%